Relationship investment in relationship marketing research: a bibliographic review - Zainol Zuraidah, Mohd Yasin Norjaya, Nik Hashim Nik M. Hazrul, Omar Nor Asiah, (N/A, 2014)
Relationship investment in relationship marketing research: a bibliographic review by Zainol Zuraidah, Mohd Yasin Norjaya, Nik Hashim Nik M. Hazrul, Omar Nor Asiah,